Chemistry: An Atoms First Approach, 3rd Edition - Steven Zumdahl (Cengage Learning, 2020)
Packed with the information, examples and problems you need to learn to ""think like a chemist,"" CHEMISTRY: AN ATOMS FIRST APPROACH, Third Edition is designed to help you become an independent problem-solver. The text begins with coverage of the atom and proceeds through the concept of molecules, structure and bonding. This approach, different from your high school course, will help you become an adept critical thinker and a strong problem-solver -- skills that will be useful to you in any career. Important Notice: Media content referenced within the product description or the product text may not be available in the ebook version.